Research on the noise pollution from different vehicle categories in the urban area - Danilevičius, Algimantas; Karpenko, Mykola; Křivánek, Vítězslav (Transport, 2023)
The noise pollution inside urban areas is one of the common problems for the inhabitants. The different levels of a noise are generated from the large amount of sources, including traffic flow on a road of urban areas. Therefore, it is essential to measure and evaluate the road traffic noise in urban areas and its population exposure in order to obtain models of a traffic noise as well as the noise mapping. The current research includes establishing a traffic noise from the different types of vehicles caused by the speed in urban areas and different road pavements (dry, wet and covered with a snow) with generalising the obtained data for more accurate using in future traffic noise models and the noise mapping. The study region is Vilnius (Lithuania), the speed range for different categories of the vehicles in the collected data is 40…130 km/h, with wide ranges of a noise level 20…180 dB. The approach presented in this research of experimental measurements is based on Statistical Pass-By (SPB) method with data proceeding upon implementation of Pearson correlation coefficient. In course of the analysis of the obtained results, it was found that the level of the curves of noise depends on the vehicles’ speed what corresponds to the best-measured values and can be used in the traffic noise models and the noise mapping.